Metal matrix composite material for drill bit

By using a mixture of major metal particles, metal carbide particles and fused carbide particles in the ground drill bit, the problem of fragility of existing drill bits is solved, and higher fracture strength, corrosion resistance and fracture toughness are achieved, improving the robustness and reliability of the drill bit.

CN119731403APending Publication Date: 2025-03-28KENNAMETAL INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380060649.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-16
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The metal matrix composite materials of existing ground drill bits are fragile and prone to rupture, causing the drill bit to fail, need to be repaired or replaced, and it is difficult to improve its robustness and reliability.

Method used

A mixture of metal matrix composite material particles containing major metal particles, metal carbide particles and substantially spherical fused carbide particles is used to form a stronger and more reliable drill bit material through specific particle ratios and the use of binders.

Benefits of technology

The lateral fracture strength, corrosion resistance and fracture toughness of metal matrix composites are improved, the overall performance of the drill bit is enhanced, and the risks of fracture and failure are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731403A_ABST
    Figure CN119731403A_ABST
Patent Text Reader

Abstract

Disclosed is a metal matrix composite particle mixture comprising (a) primary tungsten metal particles; (b) metal carbide particles; (c) substantially spherical fused carbide particles; and (d) a binder. The invention also provides a metal matrix composite material. The metal matrix composite material comprises a mixture of metal matrix composite material particles disclosed herein and a binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to metal matrix composite materials for earth-engraving drill bits. Background Art

[0002] Earth-drilling drill bits having a drill bit body or a portion thereof containing a metal matrix composite (MMC) can be used for mining and drilling, such as for mining minerals and hydrocarbon resources. For example, the drill bit can be used in the oil and gas drilling industry. The drill bit body typically contains one or more cutting elements, such as polycrystalline diamond cutting blades, embedded in or carried by the MMC. The drill bit body is typically formed by positioning the cutting elements in a mold, filling the mold with a matrix powder mixture, and then infiltrating the matrix powder mixture with a binder to form the MMC. The MMC typically contains a ceramic component, which may make the MMC brittle and prone to cracking. Such cracking may cause the drill bit to fail, requiring repair or replacement. It is expected that the drill bit containing the MMC is stronger and more reliable. Summary of the invention

[0003] The present invention provides a metal matrix composite material for an earth-moving drill bit. The metal matrix composite material comprises a metal matrix composite particle mixture, wherein the metal matrix composite particle mixture comprises primary metal particles, metal carbide particles, substantially spherical fused carbide particles and a binder.

[0004] The present invention also provides a metal matrix composite particle mixture for a drill bit, wherein the metal matrix composite particle mixture comprises a mixture of main metal particles, metal carbide particles and substantially spherical fused carbide particles.

[0005] The present invention further provides a metal matrix composite material for a drill bit. The metal matrix composite material comprises a metal matrix composite particle mixture, the metal matrix composite particle mixture comprising: primary metal particles, the primary metal particles comprising 30% to 50% by weight of tungsten, wherein the primary metal particles have an average particle size of less than 20 microns; 30% to 50% by weight of metal carbide particles, wherein the average particle size of the metal carbide particles is 20 to 45 microns; 10% to 20% by weight of substantially spherical fused carbide particles, wherein the average particle size of the substantially spherical fused carbide particles is 150 to 400 microns; and secondary metal particles, the secondary metal particles comprising 2% to 8% by weight of nickel, wherein the average particle size of the secondary metal particles is 3 to 7 microns; and a metal binder. BRIEF DESCRIPTION OF THE DRAWINGS

[0006] Figure 1is a photomicrograph image at 200X magnification of a coarse-grained tungsten carbide powder that can be used to produce the metal matrix composite material of the present invention.

[0007] Figure 2 is a photomicrograph image at 500X magnification of a coarse-grained tungsten carbide powder that can be used to produce the metal matrix composite material of the present invention.

[0008] Figure 3 is a photomicrograph image at 200X magnification of tungsten powder that can be used to produce the metal matrix composite material of the present invention.

[0009] Figure 4 is a photomicrograph image at 500X magnification of tungsten powder that can be used to produce the metal matrix composite material of the present invention.

[0010] Figure 5 is a photomicrograph image at 100X magnification of a spherical fused carbide particle powder that can be used to produce the metal matrix composite material of the present invention.

[0011] Figure 6 is a photomicrograph image at 200X magnification of a spherical fused carbide particle powder that can be used to produce the metal matrix composite material of the present invention.

[0012] Figure 7 is a micrograph of Sample 1 of the MMC of Example 1 at 100X magnification.

[0013] Figure 8 is a micrograph of Comparative Sample 1 of the MMC of Example 2 at 100X magnification.

[0014] Fig. 9 is a micrograph of Comparative Sample 2 of the MMC of Example 2 at 100X magnification.

[0015] Fig.10 is a graph of the transverse rupture strength (TRS) of the MMC samples of the present invention and the comparative MMC samples against erosion.

[0016] Fig.11 is a graph of TRS thermal shock resistance (TSR) versus TRS in W / m for MMC samples of the present invention and comparative MMC samples.

[0017] Fig.12 The fracture toughness of the MMC sample of the present invention and the comparative MMC sample is relative to TSR in W / m 1 / 2 Graph of fracture toughness in units. DETAILED DESCRIPTION

[0018] The present disclosure relates to a metal matrix composite material for a drill bit. The metal matrix composite material comprises a metal matrix composite particle mixture, wherein the metal matrix composite particle mixture comprises (a) main metal particles; (b) metal carbide particles; and (c) substantially spherical fused carbide particles.

[0019] The present disclosure also relates to a metal matrix composite particle mixture for a drill bit. The metal matrix composite particle mixture comprises a mixture of: (a) primary metal particles; (b) metal carbide particles; (c) substantially spherical fused carbide particles; and a binder.

[0020] As described above, the metal matrix composite particle mixture may include primary metal particles. The primary metal particles may include elemental tungsten, tungsten alloys, or combinations thereof. Examples of tungsten alloys include, but are not limited to, tungsten alloys containing alloying additives such as copper, nickel, iron, cobalt, molybdenum, manganese, and the like.

[0021] Based on the total weight of the metal matrix composite particle mixture, the main metal particles can be present in the metal matrix composite particle mixture in an amount of at least 15 wt%, such as at least 20 wt%, such as at least 30 wt%, such as at least 40 wt%. Based on the total weight of the metal matrix composite particle mixture, the main metal particles can be present in the metal matrix composite particle mixture in an amount of no more than 70 wt%, such as no more than 60 wt%, such as no more than 50 wt%. Based on the total weight of the metal matrix composite particle mixture, the main metal particles can be present in the metal matrix composite powder mixture in an amount of 15 wt% to 70 wt%, such as 20 wt% to 60 wt%, such as 30 wt% to 50 wt%, such as 40 wt% to 50 wt%. According to the present invention, the applicants surprisingly found that increasing the tungsten content does not reduce the corrosion resistance, and the toughness of the metal matrix composite is maximized.

[0022] The average particle size of the primary metal particles as measured by ASTM B330 may be at least 1 micron, such as at least 2.5 microns, such as at least 2.8 microns, such as at least 14 microns. The average particle size of the primary metal particles as measured by ASTM B330 may be no more than 177 microns, such as no more than 44 microns, such as no more than 20 microns, such as no more than 17 microns, such as no more than 4.8 microns. The average particle size of the primary metal particles as measured by ASTM B330 may be from 1 micron to 177 microns, such as from 2.5 microns to 44 microns, such as from 2.8 microns to 17 microns, such as from 2.8 microns to 4.8 microns, such as from 14 microns to 17 microns, such as from 1 micron to 20 microns, such as from 2.5 microns to 20 microns, such as from 14 microns to 20 microns.

[0023] The thermal conductivity of the primary metal particles may be at least 50 W / mK, such as at least 100 W / mK, such as at least 150 W / mK. The thermal conductivity of the primary metal particles may be 200 W / mK or higher. For example, when the primary metal particles comprise elemental tungsten, the thermal conductivity of the primary metal particles is about 173 W / mK.

[0024] The primary metal particles have a relatively high thermal conductivity relative to the metal carbide particles and the fused carbide particles. The metal carbide particles have a relatively high thermal conductivity relative to the fused carbide particles. The primary metal particles increase the thermal conductivity of the metal matrix composite material containing one of the metal matrix composite particle mixtures disclosed herein.

[0025] Optionally, the metal matrix composite particle mixture may include secondary metal particles. In a non-limiting example, the secondary metal particles may include nickel, iron, molybdenum, or a combination thereof. In an example, the metal matrix composite particle mixture may further include secondary metal particles including nickel powder.

[0026] Based on the total weight of the metal matrix composite particle mixture, the secondary metal particles (if present) can be present in the metal matrix composite particle mixture in an amount of at least 0.1 wt %, such as at least 0.5 wt %, such as at least 1 wt %, such as at least 2 wt %. Based on the total weight of the metal matrix composite particle mixture, the secondary metal particles can be present in the metal matrix composite particle mixture in an amount of no more than 20 wt %, such as no more than 15 wt %, such as no more than 10 wt %, such as no more than 8 wt %. Based on the total weight of the metal matrix composite particle mixture, the secondary metal particles can be present in the metal matrix composite particle mixture in an amount of 0 wt % to 20 wt %, such as 0 wt % to 15 wt %, such as 0 wt % to 10 wt %, such as 0.5 wt % to 20 wt %, such as 1 wt % to 10 wt %, such as 2 wt % to 8 wt %.

[0027] The secondary metal particles may have an average particle size of at least 1 micron, such as at least 2 microns, such as at least 3 microns, as measured by ASTM B330. The secondary metal particles may have an average particle size of no more than 25 microns, such as no more than 15 microns, such as no more than 10 microns, such as no more than 7 microns, as measured by ASTM B330. The secondary metal particles may have an average particle size of 1 micron to 25 microns, such as 2 microns to 15 microns, such as 3 microns to 10 microns, such as 3 microns to 7 microns, as measured by ASTM B330.

[0028] The metal matrix composite particle mixture may further include metal carbide particles. The metal carbide particles may include macrocrystalline tungsten carbide, conventional carburized tungsten carbide, sintered tungsten carbide, or a combination thereof.

[0029] Based on the gross weight of the metal matrix composite material particle mixture, the metal carbide particles can be present in the metal matrix composite material particle mixture in an amount of at least 20 wt %, such as at least 30 wt %, such as at least 35 wt %.Based on the gross weight of the metal matrix composite material particle mixture, the metal carbide particles can be present in the metal matrix composite material particle mixture in an amount of no more than 75 wt %, such as no more than 70 wt %, such as no more than 50 wt %.Based on the gross weight of the metal matrix composite material powder mixture, the metal carbide particles can be present in the metal matrix composite material particle mixture in an amount of 20 wt % to 75 wt %, such as 30 wt % to 70 wt %, such as 30 wt % to 50 wt %, such as 35 wt % to 50 wt %.

[0030] As measured by ASTM B822, the average particle size of the metal carbide particles is at least 0.5 micron, such as at least 10 microns, such as at least 15 microns, such as at least 20 microns. The average particle size of the metal carbide particles is no more than 74 microns, such as no more than 50 microns, such as no more than 45 microns, such as no more than 30 microns. The average particle size of the metal carbide particles is 0.5 micron to 74 microns, such as 10 microns to 50 microns, such as 15 microns to 30 microns, such as 20 microns to 45 microns. The metal carbide particles can have a faceted shape.

[0031] The metal matrix composite particle mixture may also include substantially spherical fused carbide particles. The fused carbide particles may include cast tungsten carbide, such as spherical cast fused tungsten carbide, crushed cast fused tungsten carbide, or a combination thereof.

[0032] Based on the gross weight of the metal matrix composite particle mixture, the fused carbide particles can be present in the metal matrix composite particle mixture in an amount of at least 5 wt %, such as at least 7 wt %, such as at least 10 wt %. Based on the gross weight of the metal matrix composite particle mixture, the fused carbide particles can be present in the metal matrix composite particle mixture in an amount of no more than 30 wt %, such as no more than 25 wt %, such as no more than 20 wt %. Based on the gross weight of the metal matrix composite particle mixture, the fused carbide particles can be present in the metal matrix composite particle mixture in an amount of 5 wt % to 30 wt %, such as 7 wt % to 25 wt %, such as 10 wt % to 20 wt %.

[0033] The average particle size of the fused carbide particles is at least 75 microns, such as at least 100 microns, such as at least 150 microns, as measured by ASTM B822. The average particle size of the fused carbide particles is no more than 400 microns, such as no more than 300 microns, such as no more than 250 microns. The average particle size of the fused carbide particles is from 75 microns to 400 microns, such as from 100 microns to 300 microns, such as from 150 microns to 250 microns, such as from 150 microns to 400 microns.

[0034] As previously mentioned, the fused carbide particles are substantially spherical. As used herein, "spherical" means that the particles are generally spherical with substantially no flat or concave surface areas on their convexly curved outer surfaces.

[0035] The primary metal particles have a relatively high transverse rupture strength relative to the metal carbide particles and the fused carbide particles. The metal carbide particles have a relatively high transverse rupture strength relative to the fused carbide particles. The primary metal particles increase the transverse rupture strength of a metal matrix composite material comprising one of the metal matrix composite particle mixtures disclosed herein.

[0036] The fused carbide particles have a relatively greater erosion resistance relative to the primary metal particles and the metal carbide particles. The fused carbide particles increase the erosion resistance of a metal matrix composite material comprising one of the metal matrix composite particle mixtures disclosed herein.

[0037] The fused carbide particles have a relatively high hardness relative to the main metal particles and the metal carbide particles. The metal carbide particles have a relatively high hardness relative to the main metal particles. The main metal particles have a relatively low hardness relative to the metal carbide particles and the fused carbide particles.

[0038] The primary metal particles have a relatively high fracture toughness relative to the fused carbide particles and the metal carbide particles.The primary metal particles increase the fracture toughness of a metal matrix composite material comprising one of the metal matrix composite particle mixtures disclosed herein.

[0039] As mentioned above, the present invention also relates to a metal matrix composite material comprising one of the metal matrix composite particle mixtures disclosed herein; and a metal binder.

[0040] The metal matrix composite material may comprise any of the metal matrix composite particle mixtures disclosed herein above. The metal matrix composite material may be made by any conventional technique (eg, pressing and sintering and additive manufacturing).

[0041] The metal matrix composite material may further include a metal binder. The metal binder infiltrates the metal matrix composite particle mixture and metallurgically bonds to each of the particles in the mixture. The metal binder fills the voids between the particles and bonds the particles of the metal matrix composite particle mixture together when melted during the infiltration process.

[0042] The metal binder may include a metal such as copper, manganese, nickel, zinc, tin, etc. For example, the metal binder may include a combination of copper, manganese, nickel, and zinc.

[0043] The metal matrix composite particle mixture and the metal binder may be present in the metal matrix composite in a particle to binder weight ratio of at least 0.3: 1, such as at least 0.5: 1, such as at least 0.8: 1. The particle to binder weight ratio may not exceed 5: 1, such as not exceed 3: 1, such as not exceed 2: 1. The particle to binder weight ratio may be from 0.5: 1 to 2: 1, such as from 0.3: 1 to 5: 1, such as from 0.8: 1 to 3: 1.

[0044] The metal matrix composite material may include (a) a metal matrix composite particle mixture, the metal matrix composite particle mixture comprising (i) primary metal particles, the primary metal particles comprising tungsten in an amount of 30 wt% to 50 wt%, wherein the primary metal particles have an average particle size of less than 20 microns; (ii) metal carbide particles in an amount of 30 wt% to 50 wt%, wherein the metal carbide particles have an average particle size of 20 microns to 45 microns; (iii) substantially spherical fused carbide particles in an amount of 10 wt% to 20 wt%, wherein the substantially spherical fused carbide particles have an average particle size of 150 microns to 400 microns; and (iv) secondary metal particles, the secondary metal particles comprising nickel in an amount of 2 wt% to 8 wt%, wherein the secondary metal particles have an average particle size of 3 microns to 7 microns; and (b) a metal binder.

[0045] The metal matrix composite material of the present disclosure may have a transverse rupture strength (TRS) of at least 1150 MPa, such as at least 1200 MPa, such as at least 1350 MPa, such as at least 1400 MPa, as measured by standard ASTM B406.

[0046] The metal matrix composite material of the present disclosure may have a theoretical thermal shock resistance (TSR) relative to TRS of at least 22,000 W / m, such as at least 24,000 W / m, such as at least 26,000 W / m, such as at least 28,000 W / m. For purposes of this paragraph, the theoretical thermal shock resistance relative to TRS is calculated according to the equation TSR = kTRS / Eα, where k = thermal conductivity, TRS = transverse rupture strength, E = elastic modulus or Young's modulus, and α = thermal expansion coefficient.

[0047] The theoretical thermal shock resistance of the metal matrix composite material of the present disclosure relative to the fracture toughness may be at least 700 W / m 1 / 2 , such as at least 750 W / m 1 / 2 , such as at least 800 W / m 1 / 2 For the purposes of this paragraph, theoretical thermal shock resistance relative to fracture toughness is calculated according to the equation TSR = kK1C / Eα, where k = thermal conductivity, K1C = modified E399 fracture toughness, E = elastic modulus or Young's modulus, and α = coefficient of thermal expansion.

[0048] The thermal conductivity of the metal matrix composite material of the present disclosure can be at least 40 W / mK, such as at least 45 W / mK, such as at least 50 W / mK. Thermal conductivity is calculated according to the equation k = Qd / AΔT, where Q = heat transferred, d = distance between two isothermal planes, A = surface area, and ΔT = temperature difference.

[0049] The fracture toughness of the metal matrix composite material of the present disclosure may be at least 33 MPa·m 1 / 2 , such as at least 35MPa·m 1 / 2 , such as at least 40 MPa·m 1 / 2 Fracture toughness can be measured according to the standard ASTM E399 test modified as described in Xin Deng, Jon Bitler and KK Chawla and B. Patterson, "Toughness Measurement of Cemented Carbides with Chevron-Notched Three-Point Bend Test," September 2010, Advanced Engineering Materials 12(9):948-952.

[0050] The transverse rupture strength of the metal matrix composite material may be at least 1311 MPa, such as at least 1380 MPa, such as at least 1518 MPa. The transverse rupture strength is measured according to standard ASTM B406.

[0051] The corrosion resistance of the metal matrix composite material of the present disclosure may not exceed 15 mm 3 / kg, if not exceeding 12 mm 3 / kg, if not exceeding 11 mm 3 / kg, if not exceeding 10 mm 3 / kg. Erosion resistance can be measured using the following standard procedure according to a modified ASTM G 76-04 test. Test coins are prepared by smoothing the surface of each test coin (1.5" diameter x ¼" to 3 / 8" thickness) using a machine. The coins are then dried and weighed to the nearest 0.001 grams. A high pressure tester is prepared using AFS test sand (SiO2) 50 / 70 mesh, a high pressure water pump (Hyperson HVC-20 Power Unit Series 222037), a wet sandblaster (Wet Sandblaster Model 30667) with a gun handle (Model 30342), and a nozzle (Washjet Nozzle Model MEG-SSTC-1504). The starting weight of the sand is recorded to the nearest 0.05 lb. Each test coin is placed in a fixture and secured. Each test coin is sprayed with water at a pressure of 1000 psi for 30 seconds. The final weight of the coin and the final weight of the sand are recorded. The equation (coin weight loss / density) / (sand used) = erosion factor (mm 3 For each sample, two tests were completed and the average value was taken.

[0052] Example 1

[0053] The metal matrix composite of the present invention is prepared as follows: Powders of macrocrystalline tungsten carbide, tungsten, spherical fused carbide, and nickel having average particle sizes listed in Table 1 measured according to standard ASTM testing procedures are mixed together in the amounts shown in Table 1.

[0054] Table 1

[0055]

[0056] Figure 1 and 2 The micrograph images of the coarse-grained tungsten carbide powder at 200X and 500X magnifications are shown in FIG. Figure 3 and 4 Micrograph images of tungsten powder at 200X and 500X magnifications are shown in FIG. Figure 5 and6 Micrograph images of spherical fused carbide particles at 100X and 200X magnifications are shown in FIG.

[0057] The powders listed in Table 1 were mixed in the amounts shown and the particle mixture was impregnated with molten binder metal by known infiltration methods using 50 wt % of the metallic binder based on the total weight of the metal matrix composite. The metallic binder included a combination of copper, manganese, nickel and zinc. Figure 7 A photomicrograph image of sample No. 1 at 100X magnification is shown in FIG. Substantially spherical fused carbide particles are visible in the photomicrograph image. It can be seen that the fused carbide particles are generally spherical in shape with substantially no flat or concave surface areas on their convexly curved outer surfaces and substantially no faceted or angled edges.

[0058] Example 2

[0059] Figure 8 and 9 1 and 2 are respectively shown as microphotograph images of comparative samples No. 1 and No. 2 at 100X magnification.

[0060] Table 2

[0061]

[0062] Transverse rupture strength (TRS) test, toughness test, erosion resistance test, thermal conductivity test and hardness test were performed on samples No. 1 and No. 2 and comparative samples No. C1 and No. C2. Thermal shock resistance (TSR) relative to TRS and TSR relative to fracture toughness were calculated. The test results are shown in Table 3 below.

[0063] Table 3

[0064]

[0065] TRS is measured according to the standard ASTM B406 test. Fracture toughness is measured as described above. Erosion resistance is measured according to the erosion test described above. Thermal shock resistance relative to TRS is calculated according to the equation TSR = kTRS / Eα, where k = thermal conductivity, TRS = transverse rupture strength, E = elastic modulus or Young's modulus, and α = thermal expansion coefficient. Thermal shock resistance relative to fracture toughness is calculated according to the equation TSR = kK1C / Eα, where k = thermal conductivity, K1C = modified E399 fracture toughness, E = elastic modulus or Young's modulus, and α = thermal expansion coefficient.

[0066] Fig.10The graph provided in shows a scatter plot of TRS versus erosion resistance. Fig.11 The graph provided in shows a scatter plot of TRS as a function of TSR in W / m relative to TRS. Fig.12 The graph shown in Figure 2 shows the fracture toughness as a function of W / m 1 / 2 Scatter plot of TSR versus fracture toughness in units of .

[0067] For the purpose of the following detailed description, it should be understood that, unless clearly indicated to the contrary, the present disclosure can take various alternative changes and step sequences. In addition, except in any operating example or in the case of additional indication, all numbers such as those numerals of expression value, amount, percentage, range, sub-range and fraction can be interpreted as starting with the word "about", even if the term does not clearly appear. Therefore, unless indicated to the contrary, the numerical parameter set forth in the following specification and the appended claims is an approximate value that can be changed according to the desired property to be obtained by the present disclosure. Minimally, and without attempting to limit the application of the principle of equivalents to the scope of the claims, each numerical parameter should at least be explained according to the number of reported significant figures and by applying general rounding techniques. In the case of describing closed or open numerical ranges herein, all numerals, values, amounts, percentages, sub-ranges and fractions contained in or within the numerical range will be deemed to be specifically included in the original disclosure of the application and belong to the original disclosure, as if these numerals, values, amounts, percentages, sub-ranges and fractions have been clearly written out with their entirety.

[0068]

[0013] While the numerical ranges and parameters setting forth the broad scope of the disclosure are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0069] As used herein, unless otherwise specified, plural terms may encompass their singular counterparts and vice versa unless otherwise specified. For example, although reference is made herein to "a" binder and "an" erosion resist, combinations of these components (i.e., a plurality of these components) may be used.

[0070] Additionally, in this application, unless specifically stated otherwise, the use of "or" means "and / or" even though "and / or" may be explicitly used in some cases.

[0071] As used herein, "including", "containing" and similar terms are understood in the context of this application to be synonymous with "comprising" and are therefore open-ended and do not exclude the presence of additional undescribed or unrecited elements, materials, ingredients, or method steps. As used herein, "consisting essentially of" is understood in the context of this application to include the specified elements, materials, ingredients, or method steps and elements, materials, ingredients, or method steps that do not materially affect the basic and novel characteristics described. As used herein, "consisting of" is understood in the context of this application to exclude the presence of any unspecified elements, ingredients, or method steps.

[0072] As used herein, unless otherwise indicated, the term "substantially free" means that the particular material is not purposefully added to a mixture or composition, respectively, and is present only as a trace impurity.

[0073] Although various aspects of the present disclosure have been described in detail, it will be appreciated by those skilled in the art that various modifications and alternatives to those details may be developed based on the overall teachings of the present disclosure. Therefore, the particular arrangements disclosed are intended to be illustrative only and not to limit the scope of the present disclosure, which is given by the full scope of the claims and any and all equivalents thereof.

Claims

1. A metal matrix composite material for a drill bit, the metal matrix composite material comprising: (a) A metal matrix composite particle mixture, the metal matrix composite particle mixture comprising: (i) Main metal particles; (ii) metal carbide particles; and (iii) substantially spherical fused carbide particles; and (b) Metal binder.

2. The metal matrix composite material of claim 1, wherein the primary metal particles are present in an amount of at least 15 wt % based on the total weight of the metal matrix composite particle mixture.

3. The metal matrix composite material according to claim 1, wherein: (a) the primary metal particles are present in an amount of 15 wt % to 70 wt % based on the total weight of the metal matrix composite particle mixture; (b) the metal carbide particles are present in an amount of 20 wt % to 75 wt % based on the total weight of the metal matrix composite particle mixture; and (c) the fused carbide particles are present in an amount of 5 wt % to 30 wt % based on the total weight of the metal matrix composite particle mixture. 4 . The metal matrix composite material according to claim 1 , wherein the average particle size of the primary metal particles is 1 μm to 177 μm.

5. The metal matrix composite material of claim 1, wherein the primary metal particles comprise elemental tungsten, a tungsten alloy, or a combination thereof. The metal matrix composite material according to claim 1 , wherein the average particle size of the metal carbide particles is 0.5 μm to 74 μm.

7. The metal matrix composite material of claim 1, wherein the metal carbide particles comprise macrocrystalline tungsten carbide.

8. The metal matrix composite material of claim 1, wherein the metal carbide particles have a faceted shape.

9. The metal matrix composite material of claim 1, wherein the average particle size of the fused carbide particles is 75 microns to 400 microns.

10. The metal matrix composite material of claim 1, wherein the fused carbide particles comprise cast tungsten carbide. 11 . The metal matrix composite material according to claim 1 , wherein a weight ratio of the metal matrix composite material particle mixture to the metal binder is 0.3:1 to 5:

1.

12. The metal matrix composite material of claim 1, wherein the metal binder comprises copper, manganese, nickel, zinc, or a combination thereof.

13. The metal matrix composite of claim 1, wherein the metal matrix composite particle mixture further comprises a secondary metal.

14. The metal matrix composite of claim 13, wherein the secondary metal comprises nickel, molybdenum, iron, or a combination thereof.

15. The metal matrix composite of claim 13, wherein the secondary metal is present in an amount of 0 wt% to 20 wt% based on the total weight of the metal matrix composite particle mixture.

16. The metal matrix composite material of claim 13, wherein the secondary metal has a particle size of 1 micron to 25 microns.

17. The metal matrix composite material according to claim 1, wherein: (a) the primary metal particles contain tungsten in an amount of 30 wt % to 50 wt %, wherein the average particle size of the primary metal particles is less than 20 microns; (b) the metal carbide particles are present in an amount of 30 wt % to 50 wt %, wherein the average particle size of the metal carbide particles is 20 μm to 45 μm; (c) the substantially spherical fused carbide particles are present in an amount of 10% to 20% by weight, wherein the substantially spherical fused carbide particles have an average particle size of 150 microns to 400 microns; and (d) The metal matrix composite material further comprises secondary metal particles, the secondary metal particles comprising nickel in an amount of 2 wt % to 8 wt %, wherein the secondary metal particles have an average particle size of 3 μm to 7 μm.

18. The metal matrix composite material of claim 1, wherein the metal matrix composite material has a theoretical thermal shock resistance relative to fracture toughness of at least 700 W / m 1 / 2 , the theoretical thermal shock resistance is calculated according to the equation TSR = kK1C / Eα, where k = thermal conductivity, K1C = modified E399 fracture toughness, E = elastic modulus or Young's modulus, and α = thermal expansion coefficient.

19. The metal matrix composite of claim 1, wherein the metal matrix composite has a theoretical thermal shock resistance relative to transverse rupture strength of at least 22,000 W / m, the theoretical thermal shock resistance being calculated according to the equation TSR = kTRS / Eα, where k = thermal conductivity, TRS = transverse rupture strength, E = elastic modulus or Young's modulus, and α = coefficient of thermal expansion.

20. The metal matrix composite of claim 1, wherein the metal matrix composite has a thermal conductivity of at least 40 W / mK.

21. The metal matrix composite material according to claim 1, wherein the fracture toughness of the metal matrix composite material is at least 33 MPa·m 1 / 2 .

22. The metal matrix composite of claim 1, wherein the metal matrix composite has a transverse rupture strength of at least 1150 MPa.

23. The metal matrix composite material of claim 1, wherein the metal matrix composite material has an erosion resistance of no more than 12 mm 3 / kg.

24. The metal matrix composite material of claim 1, wherein the primary metal particles have a strength greater than a strength of the metal carbide particles and a strength of the fused carbide particles, and the metal carbide particles have a strength greater than a strength of the fused carbide particles.

25. The metal matrix composite material of claim 1, wherein the thermal conductivity of the primary metal particles is greater than the thermal conductivity of the metal carbide particles and the thermal conductivity of the fused carbide particles, and the thermal conductivity of the metal carbide particles is greater than the thermal conductivity of the fused carbide particles.

26. The metal matrix composite material of claim 1, wherein the hardness of the fused carbide particles is greater than the hardness of the metal carbide particles and the hardness of the primary metal particles, and the hardness of the metal carbide particles is greater than the hardness of the primary metal particles.

27. The metal matrix composite material of claim 1, wherein the fused carbide particles have an erosion resistance that is greater than the erosion resistance of the tungsten metal particles and the erosion resistance of the metal carbide particles.

28. A metal matrix composite particle mixture for a drill bit, the metal matrix composite particle mixture comprising a mixture of: (a) Main metal particles; (b) metal carbide particles; and (c) Essentially spherical fused carbide particles.

29. The metal matrix composite particle mixture of claim 28, wherein: (a) the primary metal particles are present in an amount of 15 wt % to 70 wt % based on the total weight of the metal matrix composite particle mixture; (b) the metal carbide particles are present in an amount of 20 wt % to 75 wt % based on the total weight of the metal matrix composite particle mixture; and (c) the fused carbide particles are present in an amount of 5 wt % to 30 wt % based on the total weight of the metal matrix composite particle mixture.

30. The metal matrix composite particulate mixture of claim 28, wherein the metal matrix composite particulate mixture is infiltrated by a metallic binder.

31. A metal matrix composite material for a drill bit, the metal matrix composite material comprising: (a) A metal matrix composite particle mixture, the metal matrix composite particle mixture comprising: (i) primary metal particles, the primary metal particles comprising tungsten in an amount of 30 wt % to 50 wt %, wherein the primary metal particles have an average particle size of less than 20 microns; (ii) metal carbide particles in an amount of 30% to 50% by weight, wherein the metal carbide particles have an average particle size of 20 microns to 45 microns; (iii) 10% to 20% by weight of substantially spherical fused carbide particles, wherein the substantially spherical fused carbide particles have an average particle size of 150 microns to 400 microns; and (iv) secondary metal particles comprising nickel in an amount of 2 wt % to 8 wt %, wherein the secondary metal particles have an average particle size of 3 μm to 7 μm; and (b) Metal binder.